Cholesterol interacts with all of the lipid in bilayer membranes. Implications for models. - Singer, M A (1990)
The interaction of cholesterol with lipid membranes has been studied by differential scanning calorimetry on liposomes, a technique which involves only the natural lipids, with no exogeneous probes. The influence of cholesterol at different molar percent concentrations c on the enthalpy delta H of the main gel to liquid crystal phase transition of saturated phosphatidylcholines of acyl chain length n = 12-20 was well represented by delta H = -9.43 + 1.01n - 0.268c kcal/mol. The linear dependence of delta H simultaneously upon chain length n and upon cholesterol concentration c shows clearly that cholesterol interacts with the deeper part of the lipids, as well as the superficial parts. This observation is not accommodated in any of the current models of cholesterol-lipid interactions.